(untitled) (Physical Education, Health and Social Sciences, 2026)
An experiment was conducted at Ornamental Horticulture Nursery, Department of Horticulture, The University of Agriculture Peshawar, Pakistan, from October 2024 to January 2025 on the performance of marigolds in response to pinching and phosphorous in a shed house. A Randomized Complete Block Design (RCBD) with a split-plot arrangement comprised of two factors with three replications. Factors of the experiment were, i.e., phosphorous levels and pinching stages. The performance of marigold in response to different phosphorus levels, i.e., 0, 1%, and 2%, while pinching stages, i.e., 1, 2, and 3 bud stages, including un-pinched plants (control) was evaluated. Experimental results indicated a significant effect of the phosphorus and pinching stages on the growth and flower production of marigolds. Among the phosphorus applications, 2% of phosphorus resulted in better growth and production of marigold. The maximum plant height (21.72 cm), number of branches per plant (8.25), stem diameter (2.58 mm), number of leaves per plant (38.8), leaf fresh weight (0.24 g), leaf chlorophyll content (29.91 SPAD), days to flowering (67.25), number of flowers per plant (6.00), flower diameter (38.62 mm), and flower fresh weight (1.04 g) were recorded in plant of marigold that received 2% phosphorus. Whereas in pinching stages, maximum plant height (22.88 cm), number of branches per plant (8.22), stem diameter (2.34 mm), number of leaves per plant (39.55), leaf fresh weight (0.19 g), leaf chlorophyll content (27.52 SPAD), number of flowers per plant (8.00), flower diameter (38.34 mm), and flower fresh weight (0.94 g) were observed in plants pinched at 3 bud stages. It is concluded that phosphorus at the rate of 2% and pinching at the 3-bud stage could be recommended for better growth and flower production of French marigold (Tagetes patula) in a shed house during autumn/winter in Peshawar conditions.